2017
DOI: 10.2147/copd.s146822
|View full text |Cite
|
Sign up to set email alerts
|

Triple therapy in COPD: new evidence with the extrafine fixed combination of beclomethasone dipropionate, formoterol fumarate, and glycopyrronium bromide

Abstract: The goals of COPD therapy are to prevent and control symptoms, reduce the frequency and severity of exacerbations, and improve exercise tolerance. The triple combination therapy of inhaled corticosteroids (ICSs), long-acting beta2 agonists (LABAs), and long-acting muscarinic antagonists (LAMAs) has become an option for maintenance treatment of COPD and as a “step-up” therapy from single or double combination treatments. There is evidence that triple combination ICS/LABA/LAMA with different inhalers improves lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 40 publications
1
27
0
1
Order By: Relevance
“…1 An important finding of this analysis is that there seems to be a treatment benefit with “free,” “open-triple,” or combination therapy in the population studied. The results from the Phase III GOLDEN studies, specifically improvements in lung function and health status, are in agreement with previously reported efficacy of triple therapies 9 , 17 19 and add to the growing body of evidence regarding the potential role of triple therapy in the clinical management of COPD. We expect the place of triple LAMA/LABA/ICS therapy within the treatment algorithm to be more clearly defined in future updates of the GOLD Report.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…1 An important finding of this analysis is that there seems to be a treatment benefit with “free,” “open-triple,” or combination therapy in the population studied. The results from the Phase III GOLDEN studies, specifically improvements in lung function and health status, are in agreement with previously reported efficacy of triple therapies 9 , 17 19 and add to the growing body of evidence regarding the potential role of triple therapy in the clinical management of COPD. We expect the place of triple LAMA/LABA/ICS therapy within the treatment algorithm to be more clearly defined in future updates of the GOLD Report.…”
Section: Discussionsupporting
confidence: 87%
“…The majority of subjects on background LABA therapy were also using ICS (range: 84%–95%), representing the subset of subjects more likely to have severe disease and airflow limitation, and with the addition of nebulized LAMA, these subjects were effectively using an open LAMA/LABA/ICS triple therapy. Recent studies have demonstrated that triple therapy plays a role in the COPD therapeutic landscape, 9 , 17 , 18 and it is a recommended treatment option for patients who experience recurrent exacerbations or continuing symptoms despite current treatment with either LAMA/LABA or LABA/ICS combination. 1 An important finding of this analysis is that there seems to be a treatment benefit with “free,” “open-triple,” or combination therapy in the population studied.…”
Section: Discussionmentioning
confidence: 99%
“…When The efficacy of triple therapy delivered by 2 inhalers or a single inhaler has been reported in several studies; 51,[64][65][66][67][68] however, single-inhaler therapy is generally preferable to avoid inhalation errors and improve adherence. 69 Table 2 summarizes clinical trial evidence for ICS-based therapy in patients with COPD. In 2 clinical trials, fluticasone 1 umeclidinium 1 vilanterol significantly improved lung function and QoL compared with placebo 1 fluticasone 1 vilanterol in patients with COPD.…”
Section: Eosinophils As Markers Of Response To Icsmentioning
confidence: 99%
“…14,17 Both were noninferiority trials. In the study carried out by Bremner and colleagues 17 14,23 Open triple versus open triple therapies Only two recent studies have evaluated two different open triple therapies showing no differences in terms of lung function, health status, rescue medication, daily activities, and exacerbations. 24,25…”
Section: Fdc Triple Therapy Versus Open Triple Therapymentioning
confidence: 99%